SECURE DOCUMENT SHARING IN ELEARNING WITH VISUAL CRYPTOGRAPHY - Chandrakanthan, Kavitha; V, Latha Parthiban (International Journal of Psychosocial Rehabilitation, 2020)
E-learning is a domain that facilitates learning through the internet using electronic devices. E-learning allows the students to learn whenever and wherever needed. Communication of materials between student and tutor is to be secured. This work introduces a novel concept of a visual cryptography-based method for secure communication in e-learning. The proposed work retrieves the secure document using standard encryption algorithm techniques The outcomes shows annotated way of e-learning content, paving way for secure transfer of materials, thereby providing student satisfaction and cost effectiveness.